Section 2: Patient Records: The Computerized Patient Record: Where Do We Stand? - Jaspers, M. W. M.; Knaup, P.; Schmidt, D. (Yearbook of Medical Informatics, 2006)
To provide an overview of trends in research, developments and implementations of the computerized patient record (CPR) of the last two years.We surveyed the medical informatics literature, spanning the years 2004-2005, focusing on publications on CPRs.The main trends revealed were: 1) the development of technologies to realize privacy and security goals or remote data entry and access to CPRs; 2) investigations into how to enhance the quality and reuse of CPR data; 3) the development and evaluation of decision support functions to be integrated with CPRs; 4) evaluations of the impact of CPRs on clinicians, patients, clinical work settings and patient outcomes; and 5) the further development and use of standards to move towards shared electronic health records (EHRs).The CPR is playing a growing part in medical informatics research and evaluation studies, but the goal of establishing a comprehensive lifelong EHR is still a long way off. In moving forward to EHRs, convergence of EHR standards seems required to realize true interoperability of health care applications. User acceptance of present-day CPRs (for all categories of users) and compatibility with work patterns has not been achieved yet, and can only be realized by giving these goals high priority. This will require substantial resources for in-depth work flow analysis, development and evaluation of CPRs. Besides this, the implementation of effective CPRs asks for health care organizations that are willing to invest in new developments and to contribute to evaluation studies, to further improve CPRs’ functionalities and enhance their use in practice.Haux R, Kulikowski C, editors. IMIA Yearbook of Medical Informatics 2006.
Keywords: Medical records systems, computerized; Computer security; Decision support systems, clinical; Evaluation studies; Health informatics, standardization